1995
DOI: 10.1002/art.1790080206
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in patients with osteoarthritis in a family practice setting

Abstract: Objective. To study the impact of osteoarthritis (OA) on all areas of a patient's health-related quality of life.Methods. The Sickness Impact Profile (SIP) was administered to a group of patients with OA selected from a family medicine setting. The results were compared to a reference population, stratified by age, and adjusted for sex.Results. OA was associated with significant impairment, and had an important impact on, healthrelated quality of life in the areas of ambulation, body care and movement, emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 17 publications
2
28
0
3
Order By: Relevance
“…It causes considerable pain, functional limitation, deterioration of health-related quality of life and, in some cases, symptoms of depression [10,18,20,22,38,42,69]. This is especially worrisome for young patients with early degenerative changes because of their high functional demands and long active lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…It causes considerable pain, functional limitation, deterioration of health-related quality of life and, in some cases, symptoms of depression [10,18,20,22,38,42,69]. This is especially worrisome for young patients with early degenerative changes because of their high functional demands and long active lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…de Bock et al have reported that older patients had a higher impact on PF when compared to younger patients. [7] Zakaria et al have reported a signifi cant negative correlation between age and PF. However, they have not provided any analysis with respect to duration of disease.…”
Section: Duration Of Osteoarthritis On Physical Functioningmentioning
confidence: 98%
“…A study on OA in primary care setting from America has reported signifi cant impact on various aspects of quality of life like physical functioning (PF), emotional behavior, sleep, etc. [7] Another similar study done in primary care setting in Malaysia has reported signifi cant impact of OA on quality of life. [8] OA was also reported to affect the psychological functioning and associated with depression among Chinese patients reporting to primary care setting.…”
Section: Introductionmentioning
confidence: 93%
“…Based on data from NHANES III and the Framingham Osteoarthritis Study, the prevalence of knee osteoarthritis in the United States is estimated to be 14% in adults 26 years of age or older, 19% in those 45 years of age or older, 37% in those 60 years of age or older, and 44% in those over 80 years of age (Dillon et al, 2006;Felson et al, 1987;Lawrence et al, 2008). Osteoarthritis can have a negative impact on health-related quality of life and psychological well-being (Axford et al, 2008;Breedveld, 2004;de Bock et al, 1995;Jinks et al, 2007;Majani et al, 2005;Salaffi et al, 2005). Patients with osteoarthritis are often limited in their ability to participate in main daily activities (eg, household duties, employment, body care, ambulation, and sleep) and to maintain their independence (de Bock et al, 1995;Jinks et al, 2007;Segal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis can have a negative impact on health-related quality of life and psychological well-being (Axford et al, 2008;Breedveld, 2004;de Bock et al, 1995;Jinks et al, 2007;Majani et al, 2005;Salaffi et al, 2005). Patients with osteoarthritis are often limited in their ability to participate in main daily activities (eg, household duties, employment, body care, ambulation, and sleep) and to maintain their independence (de Bock et al, 1995;Jinks et al, 2007;Segal et al, 2004). Patients' mental health has been shown to decrease progressively over time, and patients with more severe osteoarthritis pain are most likely to experience depression and to have difficulty coping with their disease (Axford et Pain is usually the predominant symptom of osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%